1975
DOI: 10.1073/pnas.72.4.1505
|View full text |Cite
|
Sign up to set email alerts
|

Affinity labeling of the ribosomal decoding site with an AUG-substrate analog.

Abstract: The trinucleotide AUG was condensed at the 5'-end with N-bromoacetyl-p-.aminophenylphosphate.This bromoacetylated AUG analog reacted irreversibly with the mRNA binding site of Escherichia coli 70S ribosomes. After reaction of 70S ribosomes with the AUG analog, labeled 30S subunits could be isolated that were programmed for initiation-factor-dependent binding of fMet-tRNAfMet. This shows that this AUG-affinity label reacted in the decoding site for fMet-tRNAfMet. By combination of sodium dodecyl sulfate-, Sarko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1975
1975
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…To identify the target of these γ‐secretase inhibitors, we have designed derivatives of these peptide analogues that may bind covalently and irreversibly. The N‐terminal Boc group of 1b was replaced with a bromoacetyl group, a functionality susceptible to nucleophilic attack that has been extensively employed as a means of creating affinity labels 32–37. Thus, the difluoro ketone transition‐state mimic should interact with the two active site aspartates of β‐secretase,38 while the bromoacetamide should react with any proximal nucleophilic residues (e.g., Ser, Cys, Thr) to form a stable covalent bond and irreversibly inactivate the enzyme.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify the target of these γ‐secretase inhibitors, we have designed derivatives of these peptide analogues that may bind covalently and irreversibly. The N‐terminal Boc group of 1b was replaced with a bromoacetyl group, a functionality susceptible to nucleophilic attack that has been extensively employed as a means of creating affinity labels 32–37. Thus, the difluoro ketone transition‐state mimic should interact with the two active site aspartates of β‐secretase,38 while the bromoacetamide should react with any proximal nucleophilic residues (e.g., Ser, Cys, Thr) to form a stable covalent bond and irreversibly inactivate the enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…The N-terminal Boc group of 1b was replaced with a bromoacetyl group, a functionality susceptible to nucleophilic attack that has been extensively employed as a means of creating affinity labels. [32][33][34][35][36][37] Thus, the difluoro ketone transition-state mimic should interact with the two active site aspartates of γ-secretase, 38 while the bromoacetamide should react with any proximal nucleophilic residues (e.g., Ser, Cys, Thr) to form a stable covalent bond and irreversibly inactivate the enzyme. As expected, we found that the Boc-containing 1b reversibly inhibits γ-secretase: Upon replacement with inhibitorfree media, Aβ production returned to control levels (FIG.…”
Section: Resultsmentioning
confidence: 99%
“…{4-Bromo-[2][3][4][5][6][7][8][9][10][11][12][13][14] C\acetamidophenyl)phospho} uridylyl-(3'-5')-guanylyl-(3'-5')-adenosine (V) 0.65 μπιοί compound IV in IM phosphate buffer (pH6.0) was mixed with 1.3 μηιοί 2,2'-dibromo-[2-14 C]acetic anhydride (54 Ci/mol) and allowed to react for 10 h in the dark at room temperature. The reaction mixture was subjected to descending preparative paper chromatography in solvent system B (developing time -40 h).…”
mentioning
confidence: 99%